Human Pluripotent Stem-Cell-Derived Cortical Neurons Integrate Functionally into the Lesioned Adult Murine Visual Cortex in an Area-Specific Way - Ira Espuny-Camacho; Kimmo A. Michelsen; Daniele Linaro; Angéline Bilheu; Sandra Acosta-Verdugo; Adèle Herpoel; Michele Giugliano; Afsaneh Gaillard; Pierre Vanderhaeghen (Cell Reports, 2018)
The transplantation of pluripotent stem-cell-derived neurons constitutes a promising avenue for the treatment of several brain diseases. However, their potential for the repair of the cerebral cortex remains unclear, given its complexity and neuronal diversity. Here, we show that human visual cortical cells differentiated from embryonic stem cells can be transplanted and can integrate successfully into the lesioned mouse adult visual cortex. The transplanted human neurons expressed the appropriate repertoire of markers of six cortical layers, projected axons to specific visual cortical targets, and were synaptically active within the adult brain. Moreover, transplant maturation and integration were much less efficient following transplantation into the lesioned motor cortex, as previously observed for transplanted mouse cortical neurons. These data constitute an important milestone for the potential use of human PSC-derived cortical cells for the reassembly of cortical circuits and emphasize the importance of cortical areal identity for successful transplantation.